Implementasi SMA Islam Terpadu Berbasis Boarding di Jampangkulon Sukabumi - Tedi Tedi; Siti Qomariyah; Junaidin Junaidin; M. Atep Saepul Rahman (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to analyze the implementation of the boarding school-based education system at SMA Islam Terpadu Darul Amal. The background of this research focuses on the significance of a comprehensive educational approach, one that encompasses not only academic aspects but also the development of character and morals within a structured environment steeped in Islamic values. The objective of this research is to examine how the boarding school system is applied at SMA Islam Terpadu Darul Amal and its impact on the academic, social, and personal development of the students. The research method employed is a qualitative approach with a case study design, involving data collection through in-depth interviews, participatory observation, and analysis of related documents. The findings of the study reveal that the implementation of the boarding school system at SMA Islam Terpadu Darul Amal positively influences student discipline, time management skills, social competence, and academic achievements. The vision and mission of the institution are to cultivate a generation that is intellectually capable, skilled, morally upright, and ready to contribute positively to society. This study concludes that the boarding school educational model is effective in fostering the holistic development of students, integrating both academic and character-building aspects, thus reflecting the synergy between intellectual and spiritual growth in shaping well-rounded individuals.